2010
DOI: 10.1590/s0102-86502010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a highly concentrated platelet-rich plasma on the bone repair using non-critical defects in the calvaria of rabbits

Abstract: PURPOSE: To verify the effect of highly concentrated platelet-rich plasma (hPRP) in the pathways of bone repair using non-critical defects in the calvaria of rabbits. METHODS: The hPRP was produced from collected venous blood of 21 rabbits. Four non-critical defects of 8 mm in diameter were created on the calvaria of each animal. The defects were all treated differently: autogenous particled bone (APB, group 1), autogenous particled bone associated with hPRP (APB + hPRP, group 2), isolated hPRP (group 3), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…The fibrotic frame induced by L‐PRP was consistent with the findings of previous studies . Two different hypotheses should be taken into consideration when attempting to explain the results of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fibrotic frame induced by L‐PRP was consistent with the findings of previous studies . Two different hypotheses should be taken into consideration when attempting to explain the results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…The fibrotic frame induced by L-PRP was consistent with the findings of previous studies. 54,55 Two different hypotheses should be taken into consideration when attempting to explain the results of this study. The first hypothesis involves possible platelet-collagen interactions mimicking a thrombogenic-like effect, given that the activated platelets contain specific sites for different types of collagen interaction in its cellular membrane [56][57][58][59][60] and also express TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when the potential of PRP was compared to positive controls, more heterogeneous results were reported. Several studies showed that, amongst different bone grafts, autologous bone is the gold standard for the regeneration of bony defects and adding PRP to autologous bone did not provide better bone regeneration (Aghaloo, Moy & Freymiller, ; Nagata, Messora et al., ; Oliveira Filho, Nassif, Malafaia, Ribas Filho & Ribas, ; Schlegel, Donath, Rupprecht, Falk & Zimmermann, ), with a positive effect demonstrated only during the early healing period (2–4 weeks; Nagata, Melo, et al., ; Wiltfang, Kloss, Kessler, Nkenke & Schultze‐Mosgau, ). It was also shown that interposing PRP between an autologous block graft and its bed did not confer significant benefits in terms of new bone formation (Miranda, Nary Filho, Padovan, Ribeiro & Nicolielo, ).…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira Filho et al () surprisingly found that the addition of highly concentrated PRP to autograft reduces the graft capacity of bone healing. A blood clot alone even led to a more advanced stage of calvarial bone repair than PRP alone.…”
Section: Introductionmentioning
confidence: 99%